Coordinating morphology with behavior during development: an integrative approach from a fly perspective - Carvalho, Maria João A.; Mirth, Christen K. (Frontiers in Ecology and Evolution, 2015)
Animals in the wild live in highly variable and unpredictable environments. This variation in their habitat induces animals, at all stages of their development, to make decisions about what to eat, where to live, and with whom to associate. Additionally, animals like insect show dramatic restructuring of their morphology across life stages, which is accompanied by alterations in their behaviour to match stage-specific functions. Finally, in a process called developmental plasticity, environmental conditions feedback onto developmental mechanisms producing animals with stage-specific variation in both morphological and behavioural traits. In this review, we use examples from insects to explore the idea that animals are integrated units where stage-specific morphological and neurological traits develop together to increase individual fitness within their natural environments. We hypothesize that the same mechanisms act to alter both morphological and behavioural traits in response to the environment in which an organism develops. We review relevant findings from the fruit fly Drosophila melanogaster, combining insights from different fields like developmental biology, neurobiology and developmental plasticity. Finally, we highlight how insights drawn from D. melanogaster can be used as a model in future efforts to understand how developmental processes modify behavioural responses to environmental change in a stage-specific manner in other animals.